Effects of a dual inhibitor of angiotensin converting enzyme and neutral endopeptidase, MDL 100,240, on endocrine and renal functions in healthy volunteers - Rousso, P; Buclin, T; Nussberger, J; Décosterd, L A; La Roche, S D; Brunner-Ferber, F; Brunner, H R; Biollaz, J (Journal of hypertension, 1999)
To investigate the endocrine and renal effects of the dual inhibitor of angiotensin converting enzyme and neutral endopeptidase, MDL 100,240. A randomized, placebo-controlled, crossover study was performed in 12 healthy volunteers. MDL 100,240 was administered intravenously over 20 min at single doses of 6.25 and 25 mg in subjects with a sodium intake of 280 (n = 6) or 80 (n = 6) mmol/day. Measurements were taken of supine and standing blood pressure, plasma angiotensin converting enzyme activity, angiotensin II, atrial natriuretic peptide, urinary atrial natriuretic peptide and cyclic GMP excretion, effective renal plasma flow and the glomerular filtration rate as p-aminohippurate and inulin clearances, electrolytes and segmental tubular function by endogenous lithium clearance. Supine systolic blood pressure was consistently decreased by MDL 100,240, particularly after the high dose and during the low-salt intake. Diastolic blood pressure and heart rate did not change. Plasma angiotensin converting enzyme activity decreased rapidly and dose-dependently. In both the high- and the low-salt treatment groups, plasma angiotensin II levels fell and renin activity rose accordingly, while plasma atrial natriuretic peptide levels remained unchanged. In contrast, urinary atrial natriuretic peptide excretion increased dose-dependently under both diets, as did urinary cyclic GMP excretion. Effective renal plasma flow and the glomerular filtration rate did not change. The urinary flow rate increased markedly during the first 2 h following administration of either dose of MDL 100,240 (P < 0.001) and, similarly, sodium excretion tended to increase from 0 to 4 h after the dose (P = 0.07). Potassium excretion remained stable. Proximal and distal fractional sodium reabsorption were not significantly altered by the treatment. Uric acid excretion was increased. The safety and clinical tolerance of MDL 100,240 were good. The increased fall in blood pressure in normal volunteers together with the preservation of renal hemodynamics and the increased urinary volume, atrial natriuretic peptide and cyclic GMP excretion distinguish MDL 100,240 as a double-enzyme inhibitor from inhibitors of the angiotensin converting enzyme alone. The differences appear to be due, at least in part, to increased renal exposure to atrial natriuretic peptide following neutral endopeptidase blockade.